Penerapan Scaffolding terhadap Kesalahan Siswa Kelas VIII SMP dalam Menyelesaikan Soal Numerasi Setara AKM - Muhammad Rizal Rizqullah; Masriyah (Universitas Negeri Surabaya, 2026)
Scaffolding is assistance in the form of guidance provided by teachers or adults during learning so that students can independently solve problems and understand the concept material being studied. Numeracy problem equivalent to AKM is problem designed to assess students reasoning skills and abilities in understanding and applying mathematical operation concepts in various everyday problems with the aim of encouraging the development of their self-capacity. This study aims to describe students’ errors, forms of scaffolding, and the results of students AKM-equivalent numeracy problem after scaffolding. Data collection was carried out at SMPN 22 Surabaya in Grade 8th of the 2024/2025 academic year. The subjects of this study were 3 male students in class VIII of junior high school who made the most and varied errors grouped based on the level of students’ numeracy ability, including high ability, medium ability, and low ability. Data collection techniques by providing test problem and interviews. Data analysis techniques based on students’ error indicators. Interviews were analyzed by reducing data, presenting data, and drawing conclusions. The results obtained in this study are that the errors made by students are adjusted to the combination of numeracy problem components between cognitive and context levels with students’ error indicators. The scaffolding provided by the researcher is adjusted to students’ errors in the combination of numeracy problem components between cognitive and context levels with 3 forms of scaffolding, namely reviewing, explaining, and restructuring. The results of the study showed that students experienced an increase in scores and a decrease in making errors in solving numeracy problem equivalent to AKM after scaffolding was given. Several research subjects still repeated the same mistakes even though they had received scaffolding.